Geochemistry of Neogene Basalts in the Nghia Dan district, western Nghe An - Hoang, Nguyen; Ogasawara, Masatsugu; Huong, Tran Thi; Hung, Phan Van; Thu, Nguyen Thi; Thang, Cu Sy; Dang, Pham Thanh; Xuan, Pham Tich (Vietnam Journal of Earth Sciences, 2015)
Nghia Dan Neogene basalts occur as monogenetic volcanoes and thin lava layers (up to tens of meters thick). They are alkaline basalts and basanites, some containing mantle xenoliths such as spinel lherzolite. Compared with Tay Nguyen (Western Highlands) Cenozoic basalts (for example, Pleiku and DacNong) the Nghia Dan basalts show much lower SiO2 (45-48.5wt.%) and higher FeO*(up to 9-11 wt.%), TiO2 (2.5-3 wt.%) and CaO (9-10 wt.%); they are very high in trace element contents especially Ba, Th, Nb (up to 130 ppm), Sr (up to 2000 ppm) and Eu (up to 4 ppm). Their rare earth concentrations are high, much higher as compared to those of Tay Nguyen. Melting parameter modeling shows the Nghia Dan melts generated from about 3 - 4% partial melting of a combined garnet- spinel- lherzolite source between a pressure range of 20 to 25 Kb (about 75 km deep). The parameters are consistent with the low SiO2 and high trace element, including the rare earth, contents in the Nghia Dan basalts. High FeO*, TiO2, CaO and Sr may also be a result of interaction with mafic components in the lithospheric mantle by the mantle-derived melts on the way to the surface.References Anders, E., Grevesse, N., 1989: Abundances of the elements: meteorite and solar.GeochimicaetCosmochimicaActa 53, 197-214. Chi, C.T., Dorobek, S.L., Richter, C., Flower, M., Kikawa, E., Nguyen, Y.T., McCabe, R., 1998: Paleomagnetism of Late Neogene basalts in Vietnam and Thailand: Implications for the Post-Miocene tectonic history of Indochina. In: Flower M.F.J., Chung, S.L., Lo, C.H., (Eds.), Mantle Dynamics and Plate Interactions in East Asia. AGU Monograph, vol. 27, Washington, D.C., pp. 289-299. Cox, K. G., Bell, J. D. & Pankhurst, R. J., 1979: The Interpretation of Igneous Rocks. George Allen &Unwin. Flower, M.F.J., Tamaki, K., Hoang, N., 1998: Mantle extrusion: a model for dispersed volcanism and DUPAL-like asthenosphere in East Asia and the Western Pacific. In: M.F.J. Flower, S.L. Chung, C.H. Lo and T.Y. Lee (Editors), Mantle Dynamics and Plate Interactions inEast Asia. AGU Monograph, vol. 27, Washington, D.C., pp. 67-88. Hauri, E. H., Hart, S. R., 1994: Constraints on melt migration from mantle plumes: A trace element study of peridotite xenoliths from Savai’i, Western Samoa. Journal of Geophysical Research 99, 24301-24321. Hirose, K., Kushiro, I., 1993: Partial melting of dry peridotite at high pressure; determination of compositions of melts segregated from peridotite using aggregates of diamond. Earth Planetary Science Letter, 114, 477-489. Nguyen Hoang, 2005: Lithospheric mantle beneath Pleiku: Evidence from mantle xenoliths. Geology Series A, v. 287, pp. 8-19 (in Vietnamese with English abstract) Nguyen Hoang, Flower, M.F.J., 1998: Petrogenesis of Cenozoic basalts from Vietnam: implication for origins of a 'diffuse igneous province'. Journal of Petrology 39(3), 369-395. Nguyen Hoang, Flower, M. F. J., Carlson, R. W., 1996: Major, trace element, and isotopic compositions of Vietnamese basalts: interaction of enriched mobile asthenosphere with the continental lithosphere.Geochimica et Cosmochimica Acta 60, 4329-4351. Nguyen Hoang, Martin F.J. Flower, C. T. Chi, P.T. Xuan, H.V. Quy, T. T. Son, 2013: Collision-induced Basalt Eruptions at Pleiku and BuonMeThuot, South-Central Viet Nam. Journal of Geodynamics 69, 65-83. Nguyen Hoang, Uto, K., 2003: Geochemistry of Cenozoic basalts in the Fukuoka district (northern Kyushu, Japan), implications for asthenosphere and lithospheric mantle interaction.Chemical Geology 198, 249-268. Hofmann, A.W., 1988: Chemical differentiation of the Earth, the relationship between mantle, continental crust, and oceanic crust.Earth Planet. Sci. Lett. 90, 297-314. Johnson, K.T.M., Dick, H.J.B., Shimizu, N., 1990: Melting in the oceanic upper mantle: An ion microprobe study of diopsides in abyssal peridotites. Journal of Geophysical Research 95, 2661-2678. Kogiso, T., Hirose, K., Takahashi, E., 1998: Melting experiments on homogeneous mixtures of peridotite and basalt: application to the genesis of ocean island basalts.Earth Planet. Sci. Lett. 162, 45-61. Kushiro, I., 1996: Partial melting of a fertile mantle peridotite at high pressure, an experimental study using aggregates of diamond.In: Basu, A., Hart, S.R. (eds.), Earth Processes, Reading the Isotopic Code. Geophys.Monogr.95, 109-122, AGU. Lee, T-Y., Lo, C-H., Chung, S-L., Chen, C-Y., Wang, P-L., Liu, W-P., Nguyen Hoang, C.T. Chi, N.T. Yem, 1998: 40Ar/39Ar dating results of Neogene basalts in Vietnam and its tectonic implication. In: In: M.F.J. Flower, S.L. Chung, C.H. Lo and T.Y. Lee (Editors), Mantle Dynamics and Plate Interactions in East Asia, AGU Monograph, vol. 27, Washington, D.D., pp. 317-330. Nguyen Kinh Quoc, Nguyen Thu Giao, 1980:. Cenozoic volcanic activity in Viet Nam. Geology and Mineral Resources, v. 2, 137-151 (in Vietnamese with English abstract). Rangin, C., Huchon, P., Le Pichon, X., Bellon, H., Lepvrier, C., Roques, D., Nguyen, D.H., Phan, V.Q., 1995 : Cenozoic deformation of central and south Vietnam. Tectonophysics 251, 179-196. Tapponnier, P., Peltzer, G., Armijo, R., 1986: On the mechanics of the collision between India and Asia. In: M.P. Coward and A.C. Ries (Editors), Collision Tectonics. Geological Society of London, special publication, pp. 115-157. Tapponnier, P., Peltzer, G., Le Dain, A.Y., Armijo, R., Cobbold, P., 1982: Propagating extrusion tectonics in Asia: New insights from simple experiments with plasticine.  Geology 7, 611-616. Tu, K., Flower, M.F.J., Carlson, R.W., Zhang, M., Xie, G.H., 1992: Magmatism in the South China Basin, 1.Isotopic and trace element evidence for an endogenous Dupal mantle component. Chemical Geology 97, 47-63. Turner, S., Hawkesworth, C., 1995: The nature of the sub-continental mantle: constraints from the major element composition of continental flood basalts. Chem. Geol. 120, 295-314. Walker, D., Shibata, T., DeLong, D.E., 1979: Abyssal tholeiites from the Oceanographer Fracture Zone III. Phase equilibria and mixing. Contrib. Mineral. Petrol., 70, 111-125. Workman, R., Hart, S.R., 2005: Major and trace element composition of the depleted MORB mantle (DMM). Earth Planet Sci. Lett., 231, 53-72. Zindler, A., Hart, S.R., 1986: Chemical geodynamics.Annu. Rev. Earth Planet. Sci. 14, 493-571.